Formal Procedures for Poverty Alleviation Based on Mulgan's Public Strategy Theory in Singgahan District, Tuban - Syakira Mumtaz Sholehah; Ajeng; Nesya Vista Wibowo; Rizkya Dwijayanti (INDONESIAN JOURNAL OF SOCIAL POLITIC AND POLICY STUDIES, 2025)
Rural poverty in Indonesia, particularly in agrarian regions, remains a complex and multidimensional development challenge, one of which is in Singgahan District, Tuban Regency. This study aims to analyze the dynamics of poverty in Singgahan District, Tuban Regency using the Mulgan Public Strategy Theory framework, which encompasses five elements: purpose, environment, direction, action, and learning. The research employs a qualitative method with an exploratory participatory approach to explore the complexity of the poverty phenomenon through in-depth interviews with six informants, field observations, and documentation. The results indicate that although the village government has established strategic objectives for poverty alleviation through the enhancement of the agricultural sector and the distribution of social assistance, implementation faces various structural obstacles. The environment is marked by crisis-prone practices such as usury that entrap communities, lack of transparency in social assistance distribution, and limited access to education and healthcare services. Poverty occurs due to structural conditions within the government that are not focused on revolutionary efforts to eradicate poverty. Empowerment programs such as catfish farming and sewing training have yet to achieve optimal results, while Village-Owned Enterprises (BUMDES) and Village Cooperative Units (KUD) do not function effectively as capital solutions. Program evaluation reveals a significant gap between government claims of success and community perceptions regarding target accuracy and program sustainability. The phenomenon of brain drain, characterized by high youth migration to urban areas, indicates limited opportunities for productive economic activities in the village. This research recommends reformulating strategic objectives with measurable targets, developing climate risk mitigation infrastructure, strengthening data verification systems for aid recipients based on technology, and increasing accountability and community participation in development decision-making.